Analisis Keterampilan Dasar Mengajar Dalam Meningkatkan Efektivitas Pembelajaran - Luthfiyah Luthfiyah; Zaenal Mustakim (Universitas Palangka Raya, 2024)
The success and effectiveness of learning is determined by whether or not learning objectives and outcomes are achieved. To achieve the level of learning effectiveness, a teacher or educator must have a good understanding of the process of carrying out learning and have basic teaching skills. Teacher skills in managing learning cannot appear out of thin air. To master basic teaching skills, of course, you must go through programmed exercises or develop skills. The research method used in this journal uses the literature study method. A teacher must master teaching skills in the following areas: (1) reinforcement skills, (2) questioning skills, (3) variation skills, (4) explanation skills, (5) lesson opening and closing skills, (6) small group and individual teaching skills, (7) classroom management skills, and (8) group discussion guiding skills. Basic teaching skills as a form of professionalism which is one of the efforts to achieve an effective teaching-learning process. For example, to foster students' interest in learning. If the teacher masters the basic teaching skills well then the classroom atmosphere is not boring, conducive and fun. In the end, it has an impact on high student achievement and increases learning effectiveness.